2015
DOI: 10.17261/pressacademia.2015312956
|View full text |Cite
|
Sign up to set email alerts
|

Financial efficiency analysis in Islamic banks:

Abstract: This study uses Data Envelopment Analysis for the efficiency measurements while using the Malmquist Total Factor Productivity Index in order to measure the total factor productivity change. This study involves 4 Islamic banks operating in Turkey and 13 Islamic banks operating in Malaysia. Half of these Islamic banks operating in Turkey and Malaysia meet the technical productivity (CCR) value. In other words, half of these Islamic banks are able to use their Total Assets and Total Equities efficiently. It was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…According to Wu et al (2006) DEA is one of the methods commonly used by researchers. This method is able to produce efficiency scores that reflect input and output variables (Yildirim, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…According to Wu et al (2006) DEA is one of the methods commonly used by researchers. This method is able to produce efficiency scores that reflect input and output variables (Yildirim, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Contemporary information system (IS) researchers have increasingly directed interest and attention towards the link between information systems investment and organisational performance as many information systems studies have focused on the relationship between information systems sophistication (diversity and complexity in the use of IS) and organisational performance and found that information systems sophistication have positive impact on organisational performance (Salleh et al, 2010;Yildirim, 2015). A study on the relationship between information systems sophistication and performance measurement systems (Salleh et al, 2010) indicates that information systems sophistication is a determinant of performance measures.…”
Section: The Relationship Between Sophisticated Strategic Informationmentioning
confidence: 99%
“…Although previous studies have revealed that Islamic banks are less efficient in managerial productivity and technological adoption as compared with the conventional banks (Norbaizura et al, 2014). Notwithstanding, Islamic banks have been making efforts to adopt technology in order to attain higher productivity level for the purpose of improved performance as a result of the increased global competitiveness (Yildirim, 2015). However, the major problem of information systems adoption by Islamic banks is closely associated with lack of standards that define a real compliant Shari'ah system of banking due to a difference in Shari'ah interpretation in most countries and across most regions and sometimes within the country, depending on their individual Shari'ah advisor and his interpretation (Kuppusamy et al, 2009;Rahim and Zakaria, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research about Islamic bank productivity using the Malmquist index hasn't been done yet, especially in Indonesia, compared to conventional bank research. But several types of research related to Islamic bank productivity have been done, amongst is Abbas did research uses DEA method and Malmquist index in Islamic banking in Pakistan during 2005-2009 indicates that bank productivity is higher in 2005 until 2006 and 2008-2009. Research related to Islamic banking productivity also done by Yildirim (2015) on Islamic banking in Turkey and Malaysia, research result shows that bank productivity isn't affected by technical Efficiency Change (EFFCH). This result indicates that bank managerial efficiency hasn't been able to do banking activity properly.…”
Section: Introductionmentioning
confidence: 99%